Mobile organic biofilm process for ammonia removal under low solids retention time and low operating temperature conditions - Calda, Burcu (Environmental technology, 2025)
This study aimed to evaluate the effectiveness of mobile organic biofilm (MOB) technology for removing ammonia (NH3/NH4+, referred to as NH4+) from wastewater in low solids retention time (SRT) and low operating temperature conditions. The MOB technology is based on process intensification using a plant-based media (milled kenaf) to develop a mobile organic biofilm. In the MOB process, media is added to the aeration tanks of an activated sludge process. Two bench-scale sequencing batch reactors (SBRs) with 1.5 L volume were used to assess MOB technology, a control, and a MOB-added reactor, hereafter the MOB reactor. The NH4+ concentration in the influent ranged from 5.5 to 14.9 mg N/L, with an average of 10.1 mg N/L over the study period. The COD level varied from 66.0 to 94.0 mg/L, with an average of 78.8 mg/L. The results showed that the MOB process effectively removes NH4+ and COD with a three-day SRT at 12 °C. The MOB reactor achieved an average of 93.1% NH4+ and over 47% COD removal throughout the stable operation period. MOB represents a promising wastewater treatment technology for the removal of nitrogen in activated sludge facilities